These were the Greeks - Amos, H. D. (Hugh Desmond), 1933-; Lang, A. G. P. (Andrew George Paul), 1939- (Chester Springs, Pa. : Dufour Editions, 1982)
Discusses the land, history, government, economy, culture, and people of ancient Greece.
Includes index.
Bibliography: p. 222-223.
Keywords: Greece -- Civilization -- To 146 B.C.